Emotion dysregulation across levels of substance use. (February 2021) - Garke, Maria Å.; Isacsson, Nils Hentati; Sörman, Karolina; Bjureberg, Johan; Hellner, Clara; Gratz, Kim L.; Berghoff, Christopher R.; Sinha, Rajita; Tull, Matthew T.; Jayaram-Lindström, Nitya
Highlights: 2 Emotion regulation and substance use were assessed among community and inpatient individuals. 2 Emotion regulation difficulties increase as substance use severity and frequency increase. 2 Reporting more problems controlling impulsive behavior under distress was related to having a higher substance use severity and frequency. Abstract: Emotion dysregulation has shown to be of importance in the onset and maintenance of psychiatric disorders, including substance use disorders. How difficulties in emotion regulation differ across levels of substance use, and whether these relations are influenced by co-occurring psychiatric disorders, is less clear. This study aimed to identify difficulties in emotion regulation across the spectrum of substance use and evaluate the influence of co-occurring psychiatric symptoms. Self-reported emotion regulation difficulties, substance use, and other psychiatric symptoms were assessed in one community sample ( n  = 843) and two inpatient clinics, with substance use disorder populations ( n  = 415). Data were merged and analyzed with regression models and correlations. Emotion dysregulation was distributed across different levels of substance use, and significantly associated with substance use severity and frequency. High substance use severity and frequency was significantly associated with high scores on the emotion dysregulation facet specifically involving difficulties controlling impulsive behaviors. Psychiatric symptoms did not significantly influence the association between substance use and emotion dysregulation. Results indicate an association between emotion dysregulation and the frequency and severity of substance use, and also suggest that difficulties controlling impulsive behaviors may be a potentially useful treatment target for individuals with substance dependence.